Frequency selective surfaces on flexible thin plastic substrates - N. A. F. M. Zainudin; S.N. Azemi; M.F. Jamlos; A.A. Al-Hadi; P.J. Soh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The capability of the flexible substrate of the frequency selective surface (FSS) to filter out particular frequency is discussed in this paper. A new type of FSS are applied using flexible thin plastic substrate to enhance the performance of the conventional FSS that lacks of flexibility and cannot be used in bending surface. A simulation based investigation shows that the diameter or length of the square has a significant effect on the band-stop selective characteristic of the FSS. The frequency response of the band-stop are at 2.45GHz that drop at -10dB.